2017
DOI: 10.1002/elan.201700237
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Electrochemical Detection of Co(II) and Cu(II) by 1‐Diazo‐2‐Naphthol‐4‐Sulfonic Acid/MWCNTs Modified Electrode

Abstract: This work describes a simple preparation of 1‐diazo‐2‐naphthol‐4‐sulfonic acid (1,2,4‐acid) and multiwalled carbon nanotubes (MWCNTs) modified glassy carbon electrode (GCE) for the simultaneous detection of Co(II) and Cu(II). MWCNTs, with their good conductivity and large surface area, were drop‐casted onto the surface of the GCE prior to the electrodeposition of 1,2,4‐acid, a metal chelating agent. Co(II) and Cu(II) were simultaneously measured by differential pulse anodic stripping voltammetry (DPASV) in a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Up to the present time, many analysis methods have been developed to detect cobalt ions, for example, electrochemical methods, 36,37 inductively coupled plasma optical emission spectrometry (ICP-OES), 38 and colorimetric methods. 32,[39][40][41] Among these techniques, fluorometry has attracted much interest for metal sensing owing to its simplicity, high sensitivity, rapid response, low-cost detection, and convenience.…”
Section: Introductionmentioning
confidence: 99%
“…Up to the present time, many analysis methods have been developed to detect cobalt ions, for example, electrochemical methods, 36,37 inductively coupled plasma optical emission spectrometry (ICP-OES), 38 and colorimetric methods. 32,[39][40][41] Among these techniques, fluorometry has attracted much interest for metal sensing owing to its simplicity, high sensitivity, rapid response, low-cost detection, and convenience.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen from the calibration plot ( Figure 9B), there was a good linear relationship between the peak current and the logarithm of the Cu 2 + concentration in the range of 0.001 to 100 μM (I = 0.3404lnC Cu2 + + 2.6177, R 2 = 0.998), with a low detection limit of 0.457 nM (3δ). Compared with previous reports, this electrochemical sensor had a comparable low detection limit and wide linear range (Table S1) [6][7][8][9][10][38][39][40]. According to the U.S. Environmental Protection Agency (EPA), the maximum allowable concentration of copper ion in drinking water is 20 μM.…”
Section: Sensitivity Of Cu 2 + Detectionmentioning
confidence: 82%
“…Electroanalytical technique validations using ICP-OES and ICP-MS are limited in the literature. A few researchers [18][19][20], have used redissolved solution voltammetry to preconcentrate various metals, in order to provide low limits of detection and quantification. Oliveira et al [18] developed a biochar-modified carbon paste electrode for use with differential pulse adsorptive stripping voltammetry (DPAdSV) for the determination of copper (II) ions in distillate samples (cachaça, vodka, gin, and tequila).…”
Section: Introductionmentioning
confidence: 99%
“…Zamhari et al [20] reported the simultaneous electrochemical detection of Co(II) and Cu(II) by 1diazo-2-naphthol-4-sulfonic acid/MWCNTs modified glassy carbon electrode (GCE) by differential pulse anodic stripping voltammetry (DPASV) in a batch system. The method was successfully applied in real water samples and the results were in good agreement with those obtained by ICP-OES.…”
Section: Introductionmentioning
confidence: 99%